FOREST unbiased Galactic plane imaging survey with the Nobeyama 45 m telescope (FUGIN). VIII. Possible evidence of cloud–cloud collisions triggering high-mass star formation in the giant molecular cloud M 16 (Eagle Nebula). (8th September 2020) - Nishimura, Atsushi; Fujita, Shinji; Kohno, Mikito; Tsutsumi, Daichi; Minamidani, Tetsuhiro; Torii, Kazufumi; Umemoto, Tomofumi; Matsuo, Mitsuhiro; Tsuda, Yuya; Kuriki, Mika; Kuno, Nario; Sano, Hidetoshi; et al.
Abstract: M 16, the Eagle Nebula, is an outstanding H ii region which exhibits extensive high-mass star formation and hosts remarkable "pillars." We herein obtained new 12 CO J = 1–0 data for the region observed with NANTEN2, which were combined with the 12 CO J = 1–0 data obtained using the FOREST unbiased galactic plane imaging with Nobeyama 45 m telescope (FUGIN) survey. These observations revealed that a giant molecular cloud (GMC) of ∼1.3 × 10 5 M ⊙ is associated with M 16, which extends for 30 pc perpendicularly to the galactic plane, at a distance of 1.8 kpc. This GMC can be divided into the northern (N) cloud, the eastern (E) filament, the southeastern (SE) cloud, the southeastern (SE) filament, and the southern (S) cloud. We also found two velocity components (blueshifted and redshifted components) in the N cloud. The blueshifted component shows a ring-like structure, and the redshifted one coincides with the intensity depression of the ring-like structure. The position–velocity diagram of the components showed a V-shaped velocity feature. The spatial and velocity structures of the cloud indicated that two different velocity components collided with each other at a relative velocity of 11.6 km s −1 . The timescale of the collision was estimated to be ∼4 × 10 5 yr. The collision event reasonably explains the formation of the O9V star ALS 15348, as well as the shape of the Spitzer bubble N19. A similar velocity structure was found in the SE cloud, which is associated with the O7.5V star HD 168504. In addition, the complementary distributions of the two velocity components found in the entire GMC suggested that the collision event occurred globally. On the basis of the above results, we herein propose a hypothesis that the collision between the two components occurred sequentially over the last several 10 6 yr and triggered the formation of O-type stars in the NGC 6611 cluster in M 16.